A Reading on Literary Genre in the Komnenian Novels (Circe de clásicos y modernos, 2024)
This article analyzes scenes alluding to composition and reading in the preserved novels of the Komnenian period with the hypothesis that they problematize the conceptualization of literature —or at least of the novel as a genre— that circulated among intellectual groups of the 12th century. To do so, I will study the metanarrative comments present in Rhodanthe and Dosikles by Theodore Prodromos; the reading scenes depicted in Hysmine and Hysminias by Makrembolites; and finally, the literary tradition interpretation together with the composition in Drosilla and Charikles by Niketas Eugenianos.
Keywords: Komnenian period; byzantine novel; metaliterature; reception; composition